Evaluation of Haemato-Biochemical Profile of Camels Fed on Diet Supplemented with Fruit Waste - Bhatia, Tripti; Pal, Ankita; Godara , Kanta (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study evaluated the impact of fruit waste supplementation on the haemato-biochemical profile of camels. A 42-days trial was conducted with 10 camels, randomly assigned to two groups (five per group) using a randomized block design (RBD). T1 (control) received a 50:50 mix of guar and groundnut straw, while T2 was supplemented with 5% fruit waste (banana, papaya, watermelon) in the basal diet in fresh form (DM basis). Results showed significantly higher haemoglobin (p≤0.01) and packed cell volume (p≤0.05) in T2, whereas no significant changes were observed in biochemical parameters. Thus, fruit waste can be used as a cheaper feed resource at level of 5% of the diet without any adverse effects on haemato-biochemical parameters of camels.
Keywords: Biochemical profile; Camel; Fruit waste; Haematology.